The Grey behind the Golden: A Case Study of Sikkim’s Development Paradox - Gautam, Upma; Tewari, Deeksha Bajpai (International Journal of Psychosocial Rehabilitation, 2020)
When ones living place is not able to generate conducive environment for the fulfilment of the aims and aspirations of its people, it generates disharmony. People are the ones which make a place alive; unfortunately, in case of Sikkim what is falling apart is its people. Topping the ladder in terms of development indicators does not always show the ground reality. Sikkim is dangerously juxtaposed between “highs” and “lows” of development. The state has a literacy rate of 81.42% (Census of India, 2011) which is markedly higher than national average literacy rate of 74.04% (Census of India, 2011), a young favouring demographic profile where almost 47.9% are below the age of 25 years, dubious distinction of ranking second (after Tripura) in unemployment rate, increasing trend of fresh HIV cases, ranking first in the country in suicides committed, a higher rate of suicides among young people. Finally, there is an imbalance between the high economic development witnessed by the state and the jobs creation, the aspirations of the people. The gap in this mismatch is the last leg of development dilemma that the state most urgently needs to bridge. Understanding the pernicious triad of unemployment, suicide, drug abuse is thus essential in Sikkim. Through this study a comprehensive document can be generated which is able to highlight the lacunas and strength of the State’s approach towards a comprehensive resolution of the problem in Sikkim and the information further can be used for devising a working model to deal with the state’s agony.